(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kononenko S. Features of the study of electrical work in grades 7-9 of basic school. In the article the offered methodology of teaching of electrical engineering works is for students7-9 classes at the study of course of "Technology" in accordance with the operating new release of online tutorial.